Influenza A virus transactivates the mouse envelope gene encoding syncytin B and its regulator, glial cells missing 1. - Asp, L; Nellåker, C; Karlsson, H (2007)
Recently, two candidate analogs for human syncytin, denoted syncytins A and B, were identified in the murine genome. These were found to have expression patterns and functions similar to human syncytin. In addition, the identification of glial cells missing (GCM)-binding motifs in putative promoter regions of the mouse syncytins imply analogous regulation. Transcriptional modulation of syncytin by exogenous agents was recently suggested by studies reporting transactivation of syncytin in human cell lines following virus infections. The authors report that influenza A virus infection increased the levels of transcripts encoding Gcm1 and syncytin B, but not syncytin A, in NIH-3T3 cells as well as in mouse primary neurons or glia. Overexpression of human GCM1 in NIH-3T3 cells resulted in increased levels of transcripts encoding syncytin B but not syncytin A. Systemic administration of neurotropic influenza A virus resulted in a neuronal infection and increased levels of Gcm1-encoding transcripts in brains of young mice. The mouse may therefore be useful for studies on the expression and function of endogenous retroviral envelope genes and transcription factors regulating their expression in the placenta and brain during physiological or pathological conditions.